RNA thermometers in bacterial pathogens - Loh, Edmund (2019)
Temperature variation is one of the multiple parameters a microbial pathogen encounters when it invades a warm-blooded host. To survive and thrive at host body temperature, human pathogens have developed various strategies to sense and respond to their ambient temperature. An instantaneous response is mounted by RNA thermometers (RNATs), which are integral sensory structures in mRNAs that modulate translation efficiency. At low temperatures outside the host, the folded RNA blocks access of the ribosome to the translation initiation region. The temperature shift upon entering the host destabilizes the RNA structure and thus permits ribosome binding. This reversible zipper-like mechanism of RNATs is ideally suited to fine-tune virulence gene expression when the pathogen enters or exits the body of its host. This review summarizes our present knowledge on virulence-related RNATs and discusses recent developments in the field.